2018
DOI: 10.1111/jopr.12780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implant Position on Clinical and Radiographic Outcomes of Locator‐Retained Mandibular Overdentures: A 1‐Year Prospective Study

Abstract: Within the limits of this short-term clinical study, canine position for implants retaining mandibular overdentures with Locator attachments is preferred over the first premolar position, as it was associated with reduced peri-implant pocket depth and marginal bone loss after 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…30,35 For implant overdentures, no certain value has been reported as far as we know. For removable dentures, patient satisfaction has been reported to be supplied by an 8-20 N minimal amount of retention.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…30,35 For implant overdentures, no certain value has been reported as far as we know. For removable dentures, patient satisfaction has been reported to be supplied by an 8-20 N minimal amount of retention.…”
Section: Discussionmentioning
confidence: 94%
“…For removable dentures, patient satisfaction has been reported to be supplied by an 8-20 N minimal amount of retention. 30,35 For implant overdentures, no certain value has been reported as far as we know. Furthermore, the findings of a recent retrospective study showed that momentary retention forces of implant overdentures affect quality of life, but not patient satisfaction and it was pointed out that initial retention has more impact on satisfaction rather than the retention afterwards.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Implant therapy is effective and convenient for restoring missing teeth . However, since bone defects vary between patients, the implants may deviate from their ideal position or may not show the ideal inclinations . Although the stock abutments can be quickly and easily applied to the patient, the shape of the abutment can be slightly modified as needed if the implant is not in the ideal position .…”
mentioning
confidence: 99%